2016
DOI: 10.3892/mmr.2016.4830
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits growth of human non-small cell lung cancer cells via liver kinase B-1-independent activation of adenosine monophosphate-activated protein kinase

Abstract: Metformin, the most widely administered oral anti-diabetic therapeutic agent, exerts its glucose-lowering effect predominantly via liver kinase B1 (LKB1)-dependent activation of adenosine monophosphate-activated protein kinase (AMPK). Accumulating evidence has demonstrated that metformin possesses potential antitumor effects. However, whether the antitumor effect of metformin is via the LKB1/AMPK signaling pathway remains to be determined. In the current study, the effects of metformin on proliferation, cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 39 publications
8
40
0
1
Order By: Relevance
“…It was reported that AMPK acts as an upstream regulator of Foxo3a (8-10, [14][15][16]24,25). This study provided several lines of evidence that casticin activates Foxo3a in an AMPK-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…It was reported that AMPK acts as an upstream regulator of Foxo3a (8-10, [14][15][16]24,25). This study provided several lines of evidence that casticin activates Foxo3a in an AMPK-dependent manner.…”
Section: Discussionsupporting
confidence: 63%
“…Patients treated with metformin have shown a lower incidence of cancer than the other treatment groups . In addition, metformin reportedly affects various cancers, such as gastric cancer, non‐small cell lung cancer, and colorectal cancer . Metformin exerts its antitumor effects in various ways, including inducing cell cycle arrest, enhancing the immune system, inhibiting EMT, inducing hypersusceptibility for chemotherapy, and inhibiting inflammatory signals through NF‐κB/TGF‐β …”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, the impact of DM on the prognosis of patients with NSCLC could be complicated with the administration of an anti-diabetic therapeutic agent, such as metformin, which exerts its anti-diabetic effect predominantly via liver kinase B1 (LKB1)-dependent activation of adenosine monophosphate-activated protein kinase (AMPK). 38 Because it regulates the LKB-1/AMPK signal pathway, metformin has also been proven to significantly inhibit cell proliferation, induce apoptosis, and block cell cycle progression in NSCLC cells, 39 thus exerting an antitumor effect in NSCLC patients with DM. Therefore, further studies are needed to elucidate the actual interaction of DM with lung cancer.…”
Section: Discussionmentioning
confidence: 99%